Fractional-order position and force robot control - Ferreira, N. M. Fonseca (2019)
This paper presents the implementation of fractional-order algorithms both for hybrid and cascade position/force control of robotic manipulators. The systems performance and robustness is analyzed in the time domain. The impact effects of the robot gripper with the environment are also investigated.